An experimental study on the failure and enhancement mechanism of bolt-strengthening GFRP T-joint subjected to tensile loading - You Peiyu; Chen Chen; Wu Ye; Zhang Baohua; Tang Xiaojun; Zhu Dalei; Liu Zhenxue; Ma Yunsheng (Science and Engineering of Composite Materials, 2022)
The aim of this article is to investigate the failure and enhancement mechanism of bolt-strengthening glass fiber-reinforced polymer (GFRP) T-joints under quasi-static tension. One-step molding technology based on the vacuum-assisted resin infusion process is carried out to fabricate the GFRP T-joints structures. Then, a special fixture and constraint condition are set up to take the quasi-static tensile test with high reliability. Moreover, it is demonstrated that the T-joints structures may decrease their bearing capacity, resulting in interlaminar delamination at the corner region. Further, to strengthen the T-joints, the bolts are employed to effectively prevent the initiation and propagation of interlaminar delamination in the tensile loading. At the same time, as their enhancement and failure mechanisms are revealed deeply, the strengthening method is optimized as well.